2022
DOI: 10.1186/s12889-022-13131-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of metabolic and pre-metabolic syndromes using machine learning models with anthropometric, lifestyle, and biochemical factors from a middle-aged population in Korea

Abstract: Background Metabolic syndrome (MetS) is a complex condition that appears as a cluster of metabolic abnormalities, and is closely associated with the prevalence of various diseases. Early prediction of the risk of MetS in the middle-aged population provides greater benefits for cardiovascular disease-related health outcomes. This study aimed to apply the latest machine learning techniques to find the optimal MetS prediction model for the middle-aged Korean population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Our data suggest that presence of SRCs, even with incidental finding, might require a further survey of potential metabolic syndrome. Although there have been some predictive models of metabolic syndrome ( 55 57 ), clinical application of SRCs in the risk stratification needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that presence of SRCs, even with incidental finding, might require a further survey of potential metabolic syndrome. Although there have been some predictive models of metabolic syndrome ( 55 57 ), clinical application of SRCs in the risk stratification needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple other studies have been conducted with the aim of applying different ML methods to discover the optimal model for MetS prediction. One such study was performed by [15] on a Korean population (20 variables; 1 991 records), where the aim was to evaluate and compare the performances of nine different ML models based on Random Forest, Support Vector Machine, Gaussian Naïve Bayes, Decision Tree, Logistic Regression, K-nearest neighbour, Multi-layer Perceptron, eXtreme Gradient Boosting (XGBoost) and 1D Convolutional Neural Network, respectively. Results showed that the XGBoost and RF models produced the best performances, with AUC-ROC values of 0.851 and 0.844, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using one-dimensional neural networks and eight additional machine learning classifiers: A study was conducted in [ 20 ] to evaluate a dataset that describes the lifestyles, medical information, and blood tests of 1991 middle-aged Korean patients. The dataset described several metabolic syndrome indicators such as age, smoking status, sleep time, and waist circumference.…”
Section: Research Background and Related Workmentioning
confidence: 99%